2006
DOI: 10.1111/j.1466-7657.2006.00492.x
|View full text |Cite
|
Sign up to set email alerts
|

Awareness and determinants of family planning practice in Jimma, Ethiopia

Abstract: The support and encouragement for women and men to enter and complete formal education is essential in bringing about a cultural and social change in attitude towards the economic and social value of family planning. This study and others suggest that education can address the imbalance in decision making about contraception and the role of women in society generally.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

22
79
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(104 citation statements)
references
References 20 publications
22
79
3
Order By: Relevance
“…This may be due to the difference in method acceptance among the two society, health care service weakness, and nature of study area. Our study showed that 43.1% of the respondents are not used contraceptive due to fear of side effect, this showed that fear of side effect almost similar with cross-sectional study done in Baringo North District, kenya and Jimma Zone, Agaro town, which reveals fear of side effect was 25.4% [12][13][14][15]. According to our study, 23.5% respondents were not used contraceptive due to desire to have a child which is similar with a cross-sectional study done on Awareness and determinants of family planning practice in Jimma, Ethiopia, reveals that desire to have more children have major effect on modern contraceptive usage [13].…”
Section: Discussionsupporting
confidence: 54%
“…This may be due to the difference in method acceptance among the two society, health care service weakness, and nature of study area. Our study showed that 43.1% of the respondents are not used contraceptive due to fear of side effect, this showed that fear of side effect almost similar with cross-sectional study done in Baringo North District, kenya and Jimma Zone, Agaro town, which reveals fear of side effect was 25.4% [12][13][14][15]. According to our study, 23.5% respondents were not used contraceptive due to desire to have a child which is similar with a cross-sectional study done on Awareness and determinants of family planning practice in Jimma, Ethiopia, reveals that desire to have more children have major effect on modern contraceptive usage [13].…”
Section: Discussionsupporting
confidence: 54%
“…About a third of the Ethiopian women in the study perceived childbirth and childrearing to be primarily women's responsibility although almost all of them agreed that their spouses should accompany them for antenatal health care visits and childbirth. The women's roles in traditional Ethiopian culture are mainly to take care of children and manage housework whereas husbands are the dominant figure in family who make decisions [10,14]. This cultural expectation of women's roles excludes involvement of their husbands in childbirth or childrearing.…”
Section: Discussionmentioning
confidence: 99%
“…As demonstrated in a study from Ethiopia showing women's awareness on contraceptives was significantly correlated with their family planning practice [10], understanding women's perceptions about health or health problems should be the first step in carring out a health intervention for them in a community. Of socio-demographic factors, education level was found to be a significant factor affecting antenatal care and institutional delivery [11] and contraceptive use [10] in Ethiopia.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Beekle in a study on awareness and determinants of family planning practice has shown that knowledge and access to the services alone could not be adequate for acceptance of contraceptive devices. Furthermore, in developing countries, where women are dependent upon old traditions and social constraints, knowledge and awareness about family planning acceptance would not be the only decisive factor as well as the reduction in reproductivity rate (Beekle & McCabe, 2006). A study in the United States shows that there are a series of complicated factors for non-use or ineffective use of contraceptive methods among Hispanic women.…”
Section: Introductionmentioning
confidence: 99%